The diabetic ankle fracture, should we treat them differently? - Che Ahmad, Aminudin (Malaysian Orthopaedic Association and ASEAN Orthopaedic Association, 2017)
The fractures involving the ankle are common injuries that treated by orthopaedic surgeons. Patients with diabetes who sustain an ankle fracture are at increased risk for complications including higher rates of in hospital mortality, in-hospital postoperative complications and length of stay. There is special concern about the surgical treatment of closed ankle fractures in the diabetic population due to the belief that there may be a greater risk of infection and complications. Medical literature supports the fact that diabetes mellitus impairs the patient's immune, renal, vascular and nervous systems leading to chronic complications. A common problem in the diabetic patient is the development of ulcers in the foot and ankle region secondary to sensory deficits. Frequently, these ulcers become infected and jeopardize the prognosis of the affected limb. The problem is accentuated when a bone fracture is involved because altered blood flow to the extremity retards soft tissue healing and biochemical changes impair fracture healing. Even though the diabetic foot is a well-known entity, the literature is not conclusive regarding the risk of infection in surgical management of ankle fractures in diabetic patients as compared to the non-diabetic population. The patients with uncomplicated diabetes would experience fewer complications than those patients with complicated diabetes. There are studies that show increased risk of infection in the diabetic ankle fractures. The patients who had significant neuropathy and vascular disease are at higher risk for developing complications following ankle surgery. This presentation will highlight these issues and current recommendation in treating diabetic patient with ankle fracture will be discussed.